Health Professionals’ Readiness and Its Associated Factors to Implement Electronic Medical Record System in Four Selected Primary Hospitals in Ethiopia - Awol, Shekur Mohammed (Adv Med Educ Pract, 2020)
BACKGROUND: Incorporating electronic medical record systems (EMRs) into the healthcare system is not only about modernizing the health system, but is about saving lives by facilitating communication and practicing evidence-based decision. Globally, more than 50% of EMR projects fail before they reach their target. Even though EMRs are an essential tool for health care, their adoption and utilization remains low in developing countries including Ethiopia. OBJECTIVE: The aim of this study was to determine health professionals' readiness and associated factors toward the implementation of EMRs in four selected primary hospitals in Ethiopia. METHODS: An institutionbased cross-sectional study supplemented with a qualitative approach was conducted on 414 health professionals from March 2 to May 5, 2018 in four selected primary hospitals in Ethiopia. A self-administered questionnaire was used to collect the quantitative data and in-depth interviews were employed for the qualitative data. The data were analyzed using SPSS version 20 software. Descriptive statistics, bivariable, and multivariable logistic regression analyses were done. An adjusted odds ratio (AOR) with 95% CI was used to determine the association between the determinants and the outcome variable. RESULTS: More than half (258; 62.3%) of health professionals were ready to use the electronic medical recording system. EMR knowledge (AOR = 2.64; 95% CI: [1.62, 4.29]), attitude (AOR = 1.63; 95% CI: [1.01, 2.63]), computer literacy (AOR = 3.30; 95% CI: [2.05, 5.31]), and EMR training (AOR = 3.63, ;5% CI: [1.69, 5.80]) were significantly associated with EMR readiness. CONCLUSION AND RECOMMENDATION: In general, the overall readiness of health professionals for EMR implementation was found to be low. Comprehensive packages of capacity-building are crucial to raise the level of knowledge, attitude, and computer skill among health workers.